ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN Studi Kasus Pada Poliklinik Yazri PT Pusri (Persero) Palembang - Muhammad Riska Maulana Effendi (Politeknik Negeri Sriwijaya, 2015)
This research was conducted at the Polyclinic Pusri Yazri PT (Persero) Palembang. The case study of this research is to determine patient satisfaction index in Yazri clinic. by using non-probability sampling method, the research instrument in the form of a questionnaire distributed to the patients as respondents determined by purposive sampling technique. determination of the number of samples based on the calculation of Roscoe. As for the tools used in the analysis with Microsoft Excel 2010 version, which will be converted back into service satisfaction index, and the results showed that the index patient satisfaction scores with service quality Yazri clinic located at 83 or excellent ratings.